PRIVATE TECHNIQUE OF FORMATION OF REQUIREMENTS TO INFORMATION PROTECTION SYSTEMS FROM UNAUTHORIZED ACCESS TO AUTOMATED BATH SYSTEMS USING GENETIC ALGORITHM - I. G. Drovnikova; A. A. Zmeev; E. A. Rogozin (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. Analysis of the existing methodology for the formation of requirements for information protection systems (GIS) from unauthorized access (NSD) to automated systems (AS) revealed a number of significant flaws, the main of which is the following: despite the fact that the considered method undoubtedly has theoretical significance, the same time, it can not claim practical value. This is due to the fact that in this methodology, the studies were carried out not on a specific standard (widely used certified according to the regulations of the Federal Service for Technical and Export Control of Russia) GIS, and the data on threats of unauthorized access given in it do not correspond to reality (morally obsolete), but therefore require a significant upgrade. Accepting the existing methodology as a baseline, the purpose of the article is to develop a private method of forming requirements for GIS from unauthorized access to the AU, which has practical value and allows you to formulate quantitative requirements for a wide class of certified GIS.Method. When writing the article, the methods of system analysis, evolutionary modeling, probability theory and mathematical statistics, mathematical apparatus for modeling dynamic discrete networks (E-networks), and theory of algorithms were used. The methodological basis is a systematic approach.Result. A private methodology has been developed that determines the parameters of the symbolic genetic algorithm (GA) for creating a software package for analysis, evolutionary modeling, and forming quantitative requirements for GIS from un-authorized access to speakers using the Matlab 13 application software to implement GA in the Optimization toolbox programming environment.Conclusion. The proposed private method of forming requirements for GIS from unauthorized access in the AU using GA has a theoretical significance, practical value and allows you to formulate quantitative requirements for a wide class of AS certified in a certain class of security in accordance with the requirements of current regulatory documentation.